Metode Forward Chaining Pada Sistem Pakar Diagonis Penyakit Tanaman Tomat - Prahasti Prahasti; Nofi Qurniati; Venny Novita Sari (UNIVED Press, 2024)
Agricultural extension workers need solutions to the various difficulties faced by tomato farmers with their tomato plants. The aim of this research is to produce an expert system application in diagnosing diseases in tomato plants as an effort to help the difficulties of agricultural instructors and tomato farmers regarding problems with tomato plants by utilizing information technology through the Visual Basic programming language with a MySQL database through prior definition by experts. The method used in the research is the waterfall model, meanwhile in creating the knowledge base expert system application used is the forward chaining method. The expert system application is created to produce data that is entered into the application consisting of symptom data, disease data, solution data, solution data, rule data, as well as diagnosis (consulation) data by farmers. The output from the application created produces diagnostic results for tomato plant diseases based on the symptoms entered and solutions to the diagnoses that have been made. The results of the research are that the expert system application created can be operated well with a knowledge base using the forward chaining method and rules as a knowledge base that are in accordance with the objectives